(untitled) (Research, Society and Development, 2022)
Currently, the prevalence of malignant neoplasm of the oral cavity, especially squamous cell carcinoma, has been more observed. In Brazil, oral cancer represents the fifth most prevalent malignant neoplasm among men and the seventh among women. In addition to etiological factors such as tobacco and alcohol, in recent years, human papillomavirus has also been associated with the development of head and neck cancer. Therefore, the aim of this study was to present a case report of a diagnosis of invasive poorly differentiated squamous cell carcinoma with HPV-positive oropharynx in a female patient. The case in question demonstrates the need for better screening for cancer of the oral cavity, especially in the immunocompromised population.